Implementasi Kebijakan Pengembangan Pariwisata di Pulau Lombok - Munir, Usman; Dimyati, Khudzaifah; Absori, Absori (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2018)
Lombok is one of the islands of West Nusa Tenggara province with enormous tourism potential, from nature, beaches and culture. So that if this is developed properly it will bring prosperity to the Lombok people in particular and NTB in general. Tourism development policies have not been widely felt to bring effects to welfare to the community. The purpose of this study is to provide an overview of policies and implementation of tourism development policies on tourism on the island of Lombok. Data was collected by observation and interviews. From these data, then analyzed descriptively qualitatively, the data formed becomes a description that describes a situation or event described. Based on the results of the analysis of tourism development policies in Lombok island, it is inseparable from the four tourism pillars contained in regional regulations, namely tourism, marketing, industry and institutional development. The implementation of the policy has not maximally affected the welfare of the people on the island of Lombok, and has even caused new problems in the lower classes.